Ptosis and Paresis of the Nerves III, IV, VI in Patients with Diabetes Mellitus and Hypertension: A Case Report - Wibowo, Dhiska Brilliana; Paramasitha, Ditha (Green Publisher Indonesia, 2025)
Ptosis, a condition characterized by drooping of the upper eyelid, can be caused by various factors, including muscle weakness or nerve disorders such as ocular nerve palsy. This case report presents a 54-year-old male patient who experienced ptosis in the right eyelid, along with complaints of blurred vision and double vision. The patient also had a medical history of diabetes mellitus and hypertension, both of which were not well-controlled. Upon examination, the patient had ptosis in the right eye with a vision of 20/400 and normal intraocular pressure. Treatment included methylprednisolone and citicoline, along with other medications, which led to significant improvement after five days. This case highlights the importance of optimal management of diabetes and hypertension to prevent complications such as nerve paresis. The combination of diabetes mellitus, hypertension, and nerve paresis presents a unique clinical challenge, as these conditions can exacerbate one another. Effective management requires a comprehensive and multidisciplinary approach, focusing not only on the immediate symptoms but also on long-term glycemic and blood pressure control to prevent recurrence. This case emphasizes the need for clinicians to consider the interactions between comorbid conditions in the management of ptosis caused by diabetic neuropathy. The conclusions of this study are diabetes mellitus and hypertension caused vascular ischemia which leading to isolated cranial nerve palsy in adults.